68Ga-PSMA PET/CT and volumetric morphology of PET-positive lymph nodes stratified by tumor differentiation of prostate cancer - Vinsensia, Maria; Hadaschik, Boris; Holland-Letz, Tim; Mier, Walter; Haberkorn, Uwe; Kratochwil, Clemens; Giesel, Frederik L. (Journal of nuclear medicine, 2017)
68Ga-prostate-specific membrane antigen (PSMA) PET/CT is a new method to detect early nodal metastases in patients with biochemical relapse of prostate cancer. In this retrospective investigation, the dimensions, volume, localization, and SUVmax of nodes identified by 68Ga-PSMA were correlated to their Gleason score (GS) at diagnosis. Methods: All PET/CT images were acquired 60 ± 10 min after intravenous injection of 68Ga-PSMA (mean dose, 176 MBq). In 147 prostate cancer patients (mean age, 68 y; range, 44-87 y) with prostate-specific antigen relapse (mean prostate-specific antigen level, 5 ng/mL; range, 0.25-294 ng/mL), 362 68Ga-PSMA PET-positive lymph nodes (LNs) were identified. These patients were classified on the basis of their histopathology at primary diagnosis into either low- (GS ≤ 6, well differentiated), intermediate- (GS = 7, moderately differentiated), or high-GS cohorts (GS ≥ 8, poorly differentiated prostate cancer). Using semiautomated LN segmentation software (Fraunhofer MEVIS), we measured node volume and short-axis dimensions (SADs) and long-axis dimensions based on CT and compared with the SUVmax. Nodes demonstrating uptake of 68Ga-PSMA with an SUVmax of 2.0 or more were considered PSMA-positive, and nodes with an SAD of 8 mm or more were considered positive by morphologic criteria. Results: Mean SUVmax was 13.5 (95% confidence interval [CI], 10.9-16.1), 12.4 (95% CI, 9.9-14.9), and 17.8 (95% CI, 15.4-20.3) within the low-, intermediate-, and high-GS groups, respectively. The morphologic assessment of the 68Ga-PSMA-positive LN demonstrated that the low-GS cohort presented with smaller 68Ga-PSMA-positive LNs (mean SAD, 7.7 mm; n = 113), followed by intermediate- (mean SAD, 9.4 mm; n = 122) and high-GS cohorts (mean SAD, 9.5 mm; n = 127). On the basis of the CT morphology criteria, only 34% of low-GS patients, 56% of intermediate-GS patients, and 53% of high-GS patients were considered CT positive. Overall, 68Ga-PSMA imaging led to a reclassification of stage in 90 patients (61%) from cN0 to cN1 over CT. Conclusion: 68Ga-PSMA PET is a promising modality in biochemical recurrent prostate cancer patients for N staging. Conventional imaging underestimates LN involvement compared with PSMA molecular staging score in each GS cohort. The sensitivity of 68Ga-PSMA PET/CT enables earlier detection of subcentimeter LN metastases in the biochemical recurrence setting.